Large Oncosome‐Loaded VAPA Promotes Bone‐Tropic Metastasis of Hepatocellular Carcinoma Via Formation of Osteoclastic Pre‐Metastatic Niche. Issue 31 (28th September 2022) - Zhang, Shuxia; Liao, Xinyi; Chen, Suwen; Qian, Wanying; Li, Man; Xu, Yingru; Yang, Meisongzhu; Li, Xincheng; Mo, Shuang; Tang, Miaoling; Wu, Xingui; Hu, Yameng; et al.
Abstract: Tumor‐derived extracellular vesicles (EVs) function as critical mediators in selective modulation of the microenvironment of distant organs to generate a pre‐metastatic niche that facilitates organotropic metastasis. Identifying the organ‐specific molecular determinants of EVs can develop potential anti‐metastatic therapeutic targets. In the current study, large oncosomes (LOs), atypically large cancer‐derived EVs, are found to play a crucial role in facilitating bone‐tropic metastasis of hepatocellular carcinoma (HCC) cells by engineering an osteoclastic pre‐metastatic niche and establishing a vicious cycle between the osteoclasts and HCC cells. Transmembrane protein, VAMP‐associated protein A (VAPA), is significantly enriched on LOs surface via direct interaction with LOs marker α V‐integrin. VAPA‐enriched LOs‐induced pre‐metastatic education transforms the bone into a fertile milieu, which supports the growth of metastatic HCC cells. Mechanically, LOs‐delivered VAPA integrates to plasma membrane of osteoclasts and directly interacts with and activates neural Wiskott–Aldrich syndrome protein (N‐WASP) via dual mechanisms, consequently resulting in ARP2/3 complex‐mediated reorganization of actin cytoskeleton in osteoclasts and osteoclastogenesis. Importantly, treatment with N‐WASP inhibitor 187‐1‐packaged LOs (LOs/187‐1) dramatically abolishes the inductive effect of VAPA‐enriched LOs on pre‐metastatic niche formation and precludes HCC bone metastasis. These findings reveal a plausible mechanism for bone‐tropism of HCC and can represent a potential strategy to prevent HCC bone metastasis. Abstract : Hepatocellular carcinoma (HCC)‐derived VAMP‐associated protein A (VAPA)‐enriched large oncosomes (LOs) facilitate bone metastasis (BM) via engineering an osteoclastic pre‐metastatic niche. LOs‐delivered VAPA directly activates neural Wiskott–Aldrich syndrome protein (N‐WASP) to promote ARP2/3 complex‐mediated actin cytoskeleton remolding in pre‐osteoclasts, consequently resulting in osteoclast differentiation and activation. Importantly, LOs‐packaged N‐WASP inhibitor significantly abrogates the educative effect of VAPA‐enriched LOs on HCC‐BM, which represents a potential strategy to prevent HCC‐BM.